Ultrahigh Performance Piezoelectric Energy Harvester Using Lead-Free Piezoceramics with Large Electromechanical Coupling Factor. (30th March 2023) - Chae, Yeon-Gyeong; Chae, Seok-June; Go, Su-Hwan; Kim, Eun-Ji; Park, Seok-Jung; Song, Hyunseok; Nahm, Sahn
Abstract : The output power of piezoelectric energy harvester (PEH) at the resonance frequency is dependent on the electromechanical coupling factor (k p ) of the piezoceramic, which is proportional to d 33 / ε T 33 1 / 2, where d 33 and ε T 33 are the piezoelectric change and dielectric constants, respectively. Therefore, the piezoceramic for the PEH should have a large d 33 and a small ε T 33 . [001]-texturing can be used for developing piezoceramics for PEH because it generally increases d 33 without increasing ε T 33 . The 0.96(K0.5 Na0.5 )(N1-z Sz )O3 -0.03(Bi0.5 Ag0.5 )ZrO3 -0.01SrZrO3 [KN(N1-z Sz )-BAZ-SZ] piezoceramics were textured along the [001] orientation, and the piezoceramic (z = 0.01 ) showed a large k p of 0.77, which is the largest k p for KNN-related piezoceramics reported in the literature. The cantilever-type PEH manufactured using the KN(N0.99 S0.01 )-BAZ-SZ piezoceramic exhibited a large output power density of 7.86 mW/cm 3 at resonance frequency because of its large k p . To date, this is the largest power density for PEHs manufactured utilizing lead-free piezoceramics. Hence, the [001]-textured KN(N0.99 S0.01 )-BAZ-SZ piezoceramic is an excellent candidate for PEH, and [001]-texturing is a very efficient method for developing piezoceramics for PEH.